O falso self do paciente esquizoide: entre a precariedade e a funcionalidade: um estudo winnicottiano - Lira, Ana Valéria de Sousa (2024)
This research analyzed the controversies surrounding schizoid personality, focusing on the views of two psychoanalytic theorists. One theorist sees schizoid personality with a fragile and inconsistent false self, while the other considers it to have a cohesive and functional false self. I revisited the clinical case of Margaret Little, a psychotic patient with a fragile false self who achieved great success as a physician, demonstrating a well-organized and functional false self. Winnicott highlighted the importance of early emotional development and how environmental failures can lead to the formation of a false self, impairing the individual's ability to differentiate between internal and external realities. The research also addressed the evolution of schizoid personality definitions, from Eugen Bleuler to modern classifications in the DSM and ICD. Alfredo Naffah Neto and Alfredo Painceira Plot provided distinct perspectives on the false self, with Naffah Neto emphasizing its fragility and Painceira Plot arguing its functionality as a complex adaptation to challenging environments. The findings indicate that the false self in schizoid personality is multifaceted, acting both as a defense against anxiety and as an adaptive strategy that allows for professional success despite emotional fragilities. It is possible that physicians with schizoid personality can make accurate diagnoses due to their intellectual capacity, but the lack of affective contact, combined with their psychic condition, can lead to professional performance issues over time. The study contributes to the understanding of the internal dynamics of schizoid personalities and their adaptive capabilities